Combatting Persister Cells With Substituted Indoles - Song, Sooyeon; Wood, Thomas K. (Frontiers in Microbiology, 2020)
Given that a subpopulation of most bacterial cells becomes dormant due to stress, and that the resting cells of pathogens can revive and reconstitute infections, it is imperative to find methods to treat dormant cells to eradicate infections. The dormant bacteria that are not spores or cysts are known as persister cells. Remarkably, in contrast to the original report that incorrectly indicated indole increases persistence, a large number of indole-related compounds kill persister cells. Hence, in this review, we focus on the ability of indole and substituted indoles to combat the persister cells of both pathogens and non-pathogens.